Analisis Penentuan Metode Peramalan Persediaan Bahan Baku UKM Tempe Pak Fadli di Desa Parerejo - Dzikrulloh Assofi; Misbach Munir (MES Management Journal, 2024)
This study aims to find out the right forecasting method in determining the amount of raw material needs and the amount of safety stock to minimize errors in the purchase of soybean raw materials at Pak Fadli Tempe UKM. The benefit of this research is that it can reduce the excess or shortage of raw materials through forecasting methods, as well as determine the need for the right amount of safety stock. In this study, there are 3 permalan methods used, namely moving average, exponential smoothing and naive method, as well as determining the need for safety stock of raw materials that will be used as a reference for future demand for Pak Fadli Tempe UKM. From the results of this study, it can be seen that of the 3 forecasting methods used, the best method with the smallest error value is the exponential smootihing method a = 0.1, with an error value of MAD of 90, MSE of 10,181, and MAPE of 6.9. Meanwhile, in the calculation of safety stock with a service level value of 95%, the lead time is 3 days, so that the recommended safety stock value can be known as 289 kg.